'It's like... it's me': Exploring the lived experience of clothing attachment during wear. (1st April 2019) - Fleetwood-Smith, Rebecka; Hefferon, Kate; Mair, Carolyn
Clothing and its intimate proximity to the body and self have been widely explored, and yet there is little psychological research that explores the experience of wearing items of clothing imbued with personal meanings, memories and emotions. This novel study explores the experience of actively worn items of attachment clothing from a psychological perspective. Method: due to a dearth of literature within this area, a qualitative methodology was employed. Interpretative Phenomenological Analysis (IPA) was used as the focus was to explore details of participants' experience. A homogenous sample of five participants was used. Participants were asked to wear to the interview a garment that they felt emotionally attached to and was still in use. Semi-structured interviews were used, allowing for flexibility, thus ensuring the elicitation of rich data. Results: findings demonstrated that clothing attachment is a multifaceted and rich phenomenon. The garments were appropriated and imbued with a symbolic resonance that participants accessed through wearing the attachment garment. Conclusion: results link to and extend previous literature on possession attachment and provide nuanced findings that could impact areas within both fashion literature and psychology literature.